Harnessing Foundational Digital Skills for Health Prioritization: A Cross-Sectional Analysis of Web 1.0 Information Impact - Selman Kızılkaya; Dilek Uslu; Mehtap İyisoylu (Ankara Hacı Bayram Veli Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi, 2026)
The relationship between digital engagement and health prioritization is becoming increasingly significant as individuals navigate diverse online information sources. Prior research has underscored the role of digital literacy and online behaviors in shaping health-related attitudes, yet the specific impact of technology usage skills and daily internet use on importance given to health, particularly through obtaining health information from Web 1.0, remains underexplored. The study aims to examine how varying degrees of technology usage skills and internet usage interact to influence the impact of obtaining health information from Web 1.0 on importance given to health. By focusing on these moderators, the study seeks to elucidate the optimal conditions under which online health information contributes most effectively to health prioritization. The study employs a cross-sectional survey method involving 389 participants over the age of 18 in Turkey. Data collection was conducted digitally. Hayes’ PROCESS Model 2 was applied to analyze moderated interactions, with a 95% confidence interval established through bootstrapping with 5,000 samples. The analysis showed that obtaining health information from Web 1.0 was not a significant predictor of health prioritization on its own; however, the relationship became significant only among individuals with moderate technology usage skills and moderate daily internet use. Specifically, individuals with moderate internet use (3-5 hours daily) and moderate technology skills exhibited the highest prioritization of health information, whereas low and high levels of technology skills and internet use showed diminished effects. This study suggests that digital health engagement is maximized under conditions of balanced technology use and internet engagement. These findings indicate the importance of fostering moderate digital literacy and internet use for enhancing health awareness and behavior change.